Osteoporosis-related life habits and knowledge about osteoporosis among women in Tabriz, Iran - M, Rafraf; B, Bazyun; F, Afsharnia (IIUM Medical Journal Malaysia, 2009)
Introduction: The objectives of this study were to investigate the calcium intake, physical activity level and knowledge about osteoporosis in women who attended health centers in Tabriz, Iran. Materials and Methods: Three hundred ninety-nine women of childbearing age were studied. Information was collected through face to face interviews with subjects. Results: The mean daily calcium intake was 689.08±393.15 mg. Majority of subjects had low or moderate physical activity levels. Only 8% of women reported high physical activity level. Knowledge about osteoporosis in majority of subjects (63.2%) was at moderate level. Educational status of subjects was positively correlated with calcium intake. There were no significant statistics relationship between calcium intake and physical activity with other studied variables. Conclusion: Public health programs are suggested to improve calcium intake of women and elevating healthy life styles. Establishment of educational workshops to health care providers and encourage and obligate them to proper consultation with women is suggested as a suitable approach for prevention of osteoporosis.